1998
DOI: 10.1152/ajpcell.1998.274.5.c1206
|View full text |Cite
|
Sign up to set email alerts
|

Serum deprivation induces a unique hypercontractile phenotype of cultured smooth muscle cells

Abstract: Chronic asthma is characterized by hypertrophy and hyperplasia of airway smooth muscle cells (SMC) that limit airflow by a geometric effect. Whether contractility of airway SMC is altered is not clear. Cultured cells were used as a model of hyperplasia. Phenotypic changes seen indicated conversion to a synthetic, weakly contractile type. At confluence, although limited reversal of protein changes was seen, no restoration in contractility occurred. Phenotypic modulation of postconfluent cultured airway SMC unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
77
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 19 publications
8
77
0
3
Order By: Relevance
“…This is evident following prolonged withdrawal of serum (up to 20 days) from primary cultures of confluent canine tracheal smooth muscle. A subset of these cells (~20±25% of the total) reacquire the contractile protein content, shortening velocity and elongated morphology (maximal after 15±18 days of serum deprivation) that is reminiscent of contractile cells derived from the original intact tissue [28,29]. Flow cytometric examination of their DNA content, by staining with propidium iodide, confirmed that these cells do not proliferate (S.J.…”
Section: Heterogeneity and Phenotypic Modulation Of Airway Smooth Musclementioning
confidence: 99%
“…This is evident following prolonged withdrawal of serum (up to 20 days) from primary cultures of confluent canine tracheal smooth muscle. A subset of these cells (~20±25% of the total) reacquire the contractile protein content, shortening velocity and elongated morphology (maximal after 15±18 days of serum deprivation) that is reminiscent of contractile cells derived from the original intact tissue [28,29]. Flow cytometric examination of their DNA content, by staining with propidium iodide, confirmed that these cells do not proliferate (S.J.…”
Section: Heterogeneity and Phenotypic Modulation Of Airway Smooth Musclementioning
confidence: 99%
“…The approach affords the opportunity to manipulate conditions, such as soluble biomarkers and ECM composition, to assess their effects on a defined cell population, thus eliminating many difficult-to-control variables associated with in situ and in vivo experimental models. It must be kept in mind, however, that cells in culture undergo phenotype modulation such that their contractile protein expression is quite different from that in vivo, and this could significantly alter cell mechanics [218][219][220][221][222][223][224][225][226]. Nevertheless, as a way to study the effects of mechanical strain on ASM contractility and mechanical plasticity, in vitro models offer some advantages including the ability to apply acute or chronic mechanical strain varying in magnitude, frequency and direction.…”
Section: Chronic Oscillatory Length Change In Cultured Asm Cellsmentioning
confidence: 99%
“…ASMs from individuals with asthma exhibit increased synthetic capacity (8,9), mitochondrial biogenesis (10), altered calcium homeostasis (10,11), and in some reports (10)(11)(12), but not all (13,14), increased proliferation. Critically, there is emerging evidence that ASM from individuals with asthma is hypercontractile as demonstrated by an increased velocity of contraction in response to electrical field stimulation at the single-cell level (15) and in cell populations using gel contraction assays (16).…”
mentioning
confidence: 99%